Long-term outcome of autistic spectrum disorder: a retrospective case study in a southern italian region - Francesca Felicia Operto; Federica Martino; Annalisa Rinaldi; Angelo Cerracchio; Giovanni Salvati; Mariano Orza; Claudia Lembo; Gianvito Panzarino; Claudia Di Paolantonio; Alberto Verrotti; Giovanni Farello; Giangennaro Coppola (BMC, 2017)
Abstract Background Autism Spectrum Disorder (ASD) is a complex neurodevelopmental disorder, characterized by impaired social communication and restricted and repetitive behaviours, as well as associated features including intellectual disability and impaired sensorimotor function. Despite a growing interest in this devastating disorder for families and young parents, there are no certainties as regards its aetiology, although a significant genetic background is considered to be important. Since there is little information about the social adaptation and quality of life of patients with Autism Spectrum Disorder, we decided to study and evaluate the long-term outcome and quality of life in a sample of children, adolescent and young adults. Methods This is a case study of subjects diagnosed with ASD and followed by clinics and rehabilitation centers in Campania region, in the south of Italy. The study sample was composed by 110 patients (83 males, 27 females), aged between 8.1 and 28.0 years (mean 20.6; median 21.2; SD ± 4.85), recruited in 8 rehabilitation centers of Campania region. A follow-up interview was performed by means of a questionnaire administered to the parents/caregivers of patients at a mean age of their son/daughter of 20.6 years (median 21.2 years; range 8.1-28.0). Results Reports from parents or caregivers show an overall improvement with regard to social and adaptive abilities in a group of teen-agers and young adults with ASD. Major concerns on significant quality of life parameters such as independent living, work experiences, friendships and relationships, accommodation type, recreational activities and personal autonomy were persisting. Conclusions The present study shows an overall improvement with regard to social and adaptive abilities in a large number of subjects. Considerable problems are related to autonomy, employment opportunities and social relationships of these patients. Parents need more recreational activities and continuous support with facilities for families.